KEDUDUKAN SHARIA COMPLIANCE PERBANKAN SYARIAH DI INDONESIA PERSPEKTIF YURIDIS-FILOSOFIS - Adi Astiti, Ni Nyoman; Tarantang, Jefry (AL-QARDH, 2020)
Sharia compliance is currently an important issue for sharia bank stakeholders in Indonesia. There have been many sharp criticisms from the public regarding the compliance of Islamic banks to Islamic principles, that Islamic banks in Indonesia are currently not compatible with sharia. This condition may be a positive impact of the increasingly massive socialization of Islamic banking to the public so that people are starting to become aware and have sufficient knowledge of Islamic banking, both from a juridical perspective as a regulatory framework and a solution to the legal vacuum of sharia banking regulations to ensure legal certainty, as well as a perspective. philosophical on the regulatory system that aims to create justice and benefit in Islamic banking practices.